2007
DOI: 10.2987/8756-971x(2007)23[47:ulafto]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

U.S. LABORATORY AND FIELD TRIALS OF METOFLUTHRIN (SUMIONE®) EMANATORS FOR REDUCING MOSQUITO BITING OUTDOORS1

Abstract: Metofluthrin (SumiOne is a novel, vapor-active pyrethroid that is highly effective against mosquitoes. Laboratory and field trials were conducted in the United States to evaluate the mosquito repellent activity of metofluthrin-treated paper substrates ("emanators"). Initial studies were conducted to evaluate the field performance of 900-cm(2) paper fan emanators impregnated with 160 mg metofluthrin, where Aedes canadensis was the predominant species. Emanators reduced landing rates on human volunteers by betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 4 publications
0
51
0
Order By: Relevance
“…Metofluthrin has also been shown, with aspirator collections, to provide spatial repellency to mosquitoes in outdoor shelters without walls 13,14 and in houses. [15][16][17] Furthermore, metofluthrin has significantly reduced landing rates of Aedes species, 8,9 and reduced the number of Aedes albopictus caught in Centers for Disease Control and Prevention (CDC)-type miniature mosquito traps, 18 in field trials. However, these studies failed to elucidate mosquito movement associated with metofluthrin exposure or the fate of mosquitoes after exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metofluthrin has also been shown, with aspirator collections, to provide spatial repellency to mosquitoes in outdoor shelters without walls 13,14 and in houses. [15][16][17] Furthermore, metofluthrin has significantly reduced landing rates of Aedes species, 8,9 and reduced the number of Aedes albopictus caught in Centers for Disease Control and Prevention (CDC)-type miniature mosquito traps, 18 in field trials. However, these studies failed to elucidate mosquito movement associated with metofluthrin exposure or the fate of mosquitoes after exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, mosquito coils and insecticidal vaporizing mats or liquids have been used to deter mosquitoes from biting, but these products are limited in their use by the requirement for a heat or power source to vaporize their active ingredient, commonly a synthetic pyrethroid such as d-allethrin or prallethrin. [8][9][10] Furthermore, burning mosquito coils release significant amounts of fine particulate matter and volatile organic compounds that may pose an acute and chronic risk to human health. 11 However, studies into the insecticidal activity of norchrysanthemic acid esters with high vapor activity at ambient temperature by Ujiahra and others 12 identified a synthetic pyrethroid insecticide ("metofluthrin") that doesn't require a heating source and was extremely effective at knocking down Culex pipiens pallens in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus, this result supports other previous reports that metoßuthrin-impregnated paper or plastic strips are effective at repelling mosquitoes. Lucas et al (2007) reported that in a Florida Þeld trial with metoßuthrin paper fan emanators provided 95% protection against mosquitoes (Ochlerotatus spp.). Our Þeld test results showed that the repellent device (belt-worn device) provided 79% protection against Ae.…”
Section: Discussionmentioning
confidence: 98%
“…A two-way randomized block analysis of variance was used to test for treatment effects for each count, subject, and site. Percentages of reduction in landing count or protection from bites were calculated by comparing posttreatment counts with the overall pretreatment count (Lucas et al 2007). …”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation